Peschin, Ochsenkun und die Instrumentalpraxis am Hof Ottheinrichs: Eine neue Geschichte der Orgeltabulatur Klagenfurt GV 4/3 - Lodes, Birgit (Die Musikforschung, 2019)
The provenance and dating of the 'Klagenfurt' tablature A-Kla GV 4/3, the earliest organ source written in 'New German tablature', ranges in current literature from 'Carinthia c.1560' (Apel, Johnson, Novak 2017) to 'Augsburg or Munich c.1530' (Davies 2010). Based on striking parallels to Sebastian Ochsenkun's Lautenbuch of 1558, repertorial studies, and new documents, the author can demonstrate that the almost note by note intabulations of the 'classic' vocal repertory (6-, 5-, 4-voice motets by Josquin, Moliton, LaRue, Verdelot and Senfl plus other famous pieces like "Mille regretz") were made between 1539 and 1547 by Gregor Peschin who served as court organist to the music-loving Duke Ottheinrich of Palatinate-Neuburg. His more than 100 music sources, documented in an inventory of 1544, are almost entirely lost.